PENGARUH KINERJA BALAI PENYULUHAN PERTANIAN (BPP) DALAM PENERAPAN TEKNOLOGI PENGELOLAAN TANAMAN TERPADU (PTT) DAN PENINGKATAN PRODUKSI PADI DI KABUPATEN MAGELANG - Fitrin Yunita; Sriroso Satmoko; Wiludjeng Roessali (Faculty of Animal and Agricultural Science, Diponegoro University, 2018)
This study aims to analyze the performance of agricultural extension centers, analyzing the application of PTT technology of rice, as well as analyzing the performance of Agricultural Extension Centers (BPP) in influencing the adoption of PTT and rice production in the district of Magelang. The basic method of research is quantitative descriptive survey approach. Exogenous variables in this study were BPP performance, while the endogenous variable is the adoption of PTT and rice production. The population in this study is 21 BPP in Magelang. The sampling technique used method purposive sampling. Respondents in this study a number of agricultural extension 148 and 148 farmers. Data collection techniques by observation and interviews. Analysis of the data used is Path Analysis. The results showed that the performance including the BPP in either category. Adoption PTT Rice in Magelang District including the high category. Production of rice in Magelang included in the category increased. BPP performance significantly influence farmers' adoption. Adoption PTT of Rice in Magelang Regency significantly affect rice production. BPP performance in Magelang significantly affect rice production. Increasing rice production would be done if supported by the performance of BPP and implementation optimal PTT of rice, the BPP's role should be improved through capacity building extension, the provision of infrastructure and funding to support the program in order to increase rice production, especially in the district of Magelang. Keywords: Agriculture Extension Centers (BPP); Adoption PTT of Rice; Production